Benefits and spillovers of greater competition in Europe: a macroeconomic assessment - Tamim Bayoumi; Douglas Laxton; Paolo Pesenti (European Central Bank (ECB), 2004)
Using a general-equilibrium simulation model featuring nominal rigidities and monopolistic competition in product and labor markets, this paper estimates the macroeconomic benefits and international spillovers of an increase in competition. After calibrating the model to the euro area vs. the rest of the industrial world, the paper draws three conclusions. First, greater competition produces large effects on macroeconomic performance, as measured by standard indicators. In particular, we show that differences in competition can account for over half of the current gap in GDP per capita between the euro area and the US. Second, it may improve macroeconomic management by increasing the responsiveness of wages and prices to market conditions. Third, greater competition can generate positive spillovers to the rest of the world through its impact on the terms of trade.
Keywords: C51; E31; E52; 330; competition; Markups; monetary policy; Taylor Rule